Composite material and its preparation method, electrochemical device and electronic device
Patent Information
- Application Number
- JP2023130845
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-08-10
Smart Images

Figure 0007645318000001 
Figure 0007645318000002
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of energy storage technology, more specifically to composite materials and methods for their preparation, electrochemical devices and electronic devices. [Background technology]
[0002] Electrochemical devices have the characteristics of high energy density, high operating voltage, light weight, etc., and are therefore widely used in electronic products such as mobile phones, laptops, cameras, etc. While improving the electrochemical properties of electrochemical devices, their safety properties cannot be ignored. As the requirements for the properties of electronic products increase, the requirements for the properties of electrochemical devices also gradually increase. Research has shown that the transfer of active ions between the positive and negative active materials in an electrochemical device is a central process of charging and discharging, and therefore the negative active material has a significant impact on the properties of the electrochemical device, such as energy density. In addition, conventional negative active materials, such as graphite, have safety issues due to lithium deposition on the surface of graphite, and the electrochemical device has poor kinetic properties, cycle life, and capacity properties. Summary of the Invention
[0003] The present invention provides a composite material and its preparation method, an electrochemical device and an electronic device, and the composite material has excellent dynamic properties, cycle life, capacity properties, safety properties, etc.
[0004] In a first aspect, the present invention provides a composite material, the composite material comprising a graphite particle, the composite material comprising a first region and a second region on a surface of the graphite particle, the first region being graphite and the second region comprising a hard carbon layer, the first region having a surface area of A1μm 2 The surface area of the second region is A2μm 2 When A1 and A2 are expressed as 0≦A1 / A2≦9, and when the thickness of the hard carbon layer is expressed as H nm, H is expressed as 5≦H≦500.
[0005] In some embodiments, A1 and A2 satisfy 0 < A1 / A2 ≤ 4, and / or H satisfies 5 ≤ H ≤ 200.
[0006] In some embodiments, the X-ray diffraction pattern of the composite material has characteristic diffraction peaks of hard carbon between 18° and 30°, the half-value width of the characteristic diffraction peaks of hard carbon is 4° to 12°, and the X-ray diffraction pattern of the composite material further has characteristic diffraction peaks of graphite between 26° and 27°.
[0007] In some embodiments, the Raman spectrum of the composite material has a characteristic peak D and a characteristic peak E. Let the peak intensity of the characteristic peak D be I D and the peak intensity of the characteristic peak E be I G When this is done, I D / I G satisfies 0.05 ≤ I D / I G ≤ 1.4.
[0008] In some embodiments, the raw material for the preparation of hard carbon includes an asphalt material.
[0009] In some embodiments, when the BET specific surface area of the composite material is Sm 2 / g, S satisfies 0.5 ≤ S ≤ 8.
[0010] In a second aspect, the present invention provides a method for preparing a composite material, the method including mixing a precursor asphalt material and graphite to form a mixing system, heat-treating the mixing system at a first temperature so as to melt the precursor asphalt material and coat the outer surface of the graphite to form a composite precursor, heat-treating the composite precursor at a second temperature so as to oxidatively crosslink the composite precursor to form a crosslinked precursor, and carbonizing the crosslinked precursor to obtain a composite material.
[0011] In some embodiments, the volume average particle diameter Dv50 of the precursor asphalt material is 0.5 μm to 5.0 μm, and / or the volume average particle diameter Dv50 of the graphite is 8 μm to 14 μm.
[0012] In some embodiments, when the mass content of the precursor bituminous material in the mixture is M1 wt %, and the mass content of the graphite in the mixture is M2 wt %, M1 and M2 satisfy 0.01≦M1 / M2≦1.
[0013] In some embodiments, the method further comprises providing an organic solvent to the composite precursor to dissolve organic-soluble materials in the composite precursor, and heating to remove the organic solvent. In some embodiments, the precursor bituminous material comprises one or more of petroleum asphalt, mesophase pitch, and modified asphalt, and optionally further comprises one or more of: (1) the precursor bituminous material has a softening point of 150° C. to 320° C.; (2) the precursor bituminous material has a residual carbon value of ≧50%; and (3) the precursor bituminous material has a mass content of quinoline insolubles of ≦5 wt%.
[0014] In a third aspect, the present invention provides an electrochemical device comprising an anode piece, the anode piece comprising an anode piece according to any one of the embodiments of the second aspect of the present invention.
[0015] In some embodiments, the negative electrode active material layer has a compressed density of 1.45 g / cm 3 ~1.7g / cm 3 and / or the porosity of the negative electrode active material layer is in the range of 15% to 25%.
[0016] In a fourth aspect, the present invention provides an electronic device comprising an electrochemical device according to any one of the embodiments of the second aspect of the present invention.
[0017] According to the electrochemical device of the embodiment of the present invention, the hard carbon has many defect sites, so that many lithium storage sites can be provided. By coating the surface of the graphite material with the hard carbon material, the defect sites on the surface of the graphite can be reduced, and the composite material obtained by combining the hard carbon and the graphite has excellent dynamic properties, lithium is not easily precipitated on the surface of the composite material, its safety properties are improved, and it is advantageous for improving the fast charging properties, and at the same time, the expansion and peeling of the graphite sheet layer during the lithium insertion process of the graphite material can be suppressed, and the cycle properties and capacity properties of the electrochemical device can be improved. Due to the properties of the hard carbon material, a lot of irreversible lithium loss occurs during the initial charge and discharge process, causing a loss of energy density, so the coating amount and coating area of the hard carbon are controlled to satisfy 0≦A1 / A2≦9, 5≦H≦500, thereby improving the dynamic properties and simultaneously improving the energy density and capacity properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present invention will be described in detail. Throughout the specification of the present invention, the same or similar parts and parts having the same or similar functions are indicated by similar reference numerals. The embodiments related to the drawings described herein are for the purpose of explanation, illustration, and are used to provide a basic understanding of the present invention. The embodiments of the present invention should not be construed as limiting the present invention.
[0019] It should be noted that quantities, ratios, and other values may be expressed in ranges herein. Such ranges are for convenience and brevity and should be interpreted flexibly, and such ranges not only include the numerical values expressly specified as numerical values limited to the range, but also include all values and subranges contained within the range, as if each value and subrange were expressly specified.
[0020] In specific embodiments and in the claims, a list of items connected by the terms "one or more of," "one or more of," "one or more of," or other similar terms means any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means A only, B only, or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means A only; or B only; C only; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include one element or multiple elements. Item B may include one element or multiple elements. Item C may include one element or multiple elements.
[0021] composite material A first aspect of the present invention provides a composite material, the composite material comprising a graphite particle, the graphite particle comprising a first region and a second region on a surface thereof, the first region being graphite and the second region comprising a hard carbon layer, the first region having a surface area of A1μm 2 The surface area of the second region is A2 μm 2 When A1 and A2 satisfy 0≦A1 / A2≦9, and when the thickness of the hard carbon layer is H nm, H satisfies 5≦H≦500. The inventors speculate that the action mechanism of the present invention is as follows.
[0022] The theoretical specific capacity of graphite is 372mAh / g, and the lithium ion battery prepared using graphite has the characteristics of high and stable working voltage, high initial charge / discharge efficiency and high cycle performance. Graphite includes artificial graphite and / or natural graphite, and graphite has many defects, such as low 002 crystal plane spacing and surface defect content, and under high rate charging and low temperature operating conditions, the dynamic conditions for active ions, such as lithium ions, to diffuse into graphite are poor, and lithium deposition phenomenon is likely to occur on the surface of graphite particles and penetrate the separator, which further causes safety issues. At the same time, during the long cycle process, on the one hand, graphite may expand, which may change the thickness and stress of the electrochemical device, and on the other hand, lithium ions are repeatedly released between the graphite sheet layers, which causes the graphite sheet layers to peel off, resulting in capacity loss and material destruction, which leads to poor cycle performance of the electrochemical device.
[0023] Hard carbon is a carbon material with a graphite microcrystal structure, in which the microcrystals are arranged irregularly and strong bridges exist between the microcrystals. Hard carbon has a 002 crystal plane spacing larger than 0.37 nm, and the internal microcrystals are disordered, with many defect sites, providing many lithium storage sites. By coating the surface of the graphite material with hard carbon material, the defect sites on the surface of the graphite can be reduced, and the composite material obtained by combining hard carbon with graphite has excellent dynamic properties, and lithium is not easily precipitated on the surface of the composite material, improving its safety properties and favoring the improvement of fast charging properties. At the same time, it can suppress the expansion of the graphite material and the peeling phenomenon of the graphite sheet layer during the lithium insertion process, and improve the cycle properties and capacity properties of the electrochemical device.
[0024] The thickness of the coating layer containing hard carbon can be measured by transmission electron microscopy (TEM).
[0025] Due to the characteristics of the hard carbon material, a large amount of irreversible lithium loss occurs during the first charge-discharge process, causing a loss of energy density. Therefore, it is necessary to control the coating amount and coating area of the hard carbon so that 0≦A1 / A2≦9 and 5≦H≦500 are satisfied. Thereby, while improving the kinetic characteristics, the energy density, capacity characteristics, etc. are simultaneously improved. Optionally, A1 and A2 satisfy 0<A1 / A2≦4, and H satisfies 5≦H≦200. Exemplarily, A1 / A2 may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9 or a range consisting of any two of these values. The thickness of the coating layer may be 5nm, 10nm, 20nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or a range consisting of any two of these values. In some embodiments, the X-ray diffraction pattern of the composite material has a characteristic diffraction peak of hard carbon between 18° and 30°, the half-value width of the characteristic diffraction peak of the hard carbon is 4° to 12°, and the X-ray diffraction pattern of the composite material has a characteristic diffraction peak of graphite between 26° and 27°. In some embodiments, the Raman spectrum of the composite material has a characteristic peak D and a characteristic peak E. Let the peak intensity of the characteristic peak D be I D and the peak intensity of the characteristic peak E be I G When this is done, I D / I G satisfies 0.05≦I D / I G ≦1.4. Since the composite material has both hard carbon and graphite, its Raman spectrum includes both the characteristic peak of hard carbon and the characteristic peak of graphite, and the measured I D / I G is not a fixed value, that is, it is within a specific data range.
[0026] The hard carbon may cover a part of the graphite surface or the entire graphite surface. Here, for ease of understanding, the graphite surface is divided into two regions, a first region and a second region, and the surface region of the graphite that is covered with hard carbon is defined as the second region, and the surface region of the graphite that is not covered with hard carbon is defined as the first region. The surface areas of the first region and the second region can be measured by a Raman test. The composite material is used as a sample, and the I measured by the Raman test is D / I G does not distribute fixedly within the range of 0.05 to 1.4, and when the measurement point is located in the first region, the measured I D / I G is characteristic of graphite, and when the measurement point is located in the second region, the measured I D / I G are characteristics of hard carbon. The probability that these two characteristics are measured by the Raman test is related to the ratio of the area of the graphite surface that is not covered with hard carbon and the area that is covered with hard carbon, and therefore, the present invention can measure the ratio A1 / A2 of the surface areas of the first region and the second region by the Raman test. A1 / A2=0 indicates that the entire surface of the graphite is covered with hard carbon, that is, there is no region on the surface of the graphite that is not covered with hard carbon. A1 / A2>0 indicates that a part of the surface of the graphite is covered with hard carbon, and there is a region on the surface of the graphite that is not covered with hard carbon.
[0027] In some embodiments, the hard carbon material can be obtained by treating a carbon-containing precursor material with a hydrothermal or chemical process, and the precursor material includes one or more of a precursor resin material, a precursor bituminous material, and a precursor biomass material. The precursor material of the present invention can be selected as a precursor bituminous material, and the pore structure of the bituminous hard carbon prepared from the precursor bituminous material is richer and the pore distribution is uniform, which is favorable for providing more lithium storage sites and improving the capacity of the composite material.
[0028] The inventors have found that the properties of the composite material can be further improved if the composite material further satisfies one or more of the following conditions:
[0029] In some embodiments, the specific surface area BET of the composite material is Sm 2 / g, S satisfies 0.5≦S≦8.
[0030] When the specific surface area of the composite material is within the above range, the specific surface area of the composite material can be not too high, and the electrochemical device can form an SEI film with an appropriate thickness during the initial charge / discharge process, which is less likely to cause capacity loss of the electrochemical device. In addition, the specific surface area of the composite material is not too small, the particle size of the composite material is not too large, and the diffusion path of lithium ions inside the composite material is relatively short, which is favorable for improving the rapid charge / discharge capability of the electrochemical device. Optionally, S satisfies 0.5≦S≦6. For example, the specific surface area BET of the composite material is 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, or a range consisting of any two of these values.
[0031] Method for preparing composite materials The second aspect of the invention further provides a method of preparing a composite material, which is used to prepare the composite material of the first aspect of the invention.
[0032] The method comprises: Step S100 of mixing a precursor bituminous material and graphite to form a mixed system; heat treating the mixture at a first temperature S200 to melt and coat the precursor bituminous material on an outer surface of the graphite to form a composite precursor; S300, heat treating the composite precursor at a second temperature to oxidatively crosslink the composite precursor and form a crosslinked precursor; and step S400 of carbonizing the crosslinked precursor to obtain a composite material.
[0033] The preparation process of the present invention is simple and highly efficient, and can provide composite materials with excellent properties.
[0034] In some embodiments, in step S100, when the mass content of the precursor bituminous material in the mixed system is M1 wt %, and the mass content of the graphite in the mixed system is M2 wt %, M1 and M2 satisfy 0.01≦M1 / M2≦1. By having the ratio of the mass content of the precursor bituminous material, for example, bitumen to graphite, within the above range, the mass content of bitumen is not too high, and blocking is unlikely to occur between the bituminous material particles in the subsequent melting process, so that the crushing and sieving process can be omitted, the risk of exposure of the coating interface due to crushing and sieving and deterioration of the coating effect is reduced, and the coating effect of bitumen is guaranteed. Exemplarily, the ratio of the mass content of the precursor bituminous material to the mass content of graphite may be 0.01, 0.02, 0.05, 0.8, 0.1, 0.2, 0.5, 0.6, 0.8, 1, or a range consisting of any two of the aforementioned values.
[0035] In some embodiments, in step S100, the precursor bituminous material has a volume average particle size Dv50 of 0.5 μm to 5.0 μm, and / or the graphite has a volume average particle size Dv50 of 8 μm to 14 μm. The physical definition of Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. Dv50 can be measured by methods known in the art. For example, see standard GB / T 19077.1-2016 and can be measured with a laser particle size analyzer (e.g., Malvern Master Size 3000). Exemplarily, the precursor bituminous material has a volume average particle size of 0.5 μm, 0.8 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 5.0 μm, or a range consisting of any two of the aforementioned values. The graphite may have a volume average particle size of 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or a range consisting of any two of the foregoing values.
[0036] When the volume average particle size of the precursor bitumen material is within the above range, blocking is unlikely to occur during the melting process, and the surfaces of the graphite particles can be uniformly coated, improving the coating effect.
[0037] In some embodiments, the graphite in step S100 may be selected from synthetic graphite or natural graphite. Surface defects in the graphite can be reduced by coating the outer surface of the graphite with a precursor bituminous material, such as bitumen.
[0038] In some embodiments, the precursor bituminous material in step S100 includes one or more of a precursor resin material, a precursor bituminous material, and a precursor biomass material. Illustratively, the precursor resin material includes one or more of a phenolic resin, an epoxy resin, and a polyfurfuryl alcohol, and the precursor bituminous material includes one or more of a petroleum asphalt, a mesophase pitch, and a modified asphalt, and the mesophase pitch can be obtained by a heat treatment process on coal tar pitch, a petroleum asphalt, and the like. The modified asphalt may be modified by doping with a rubber, a resin, a polymer, or a filler, or may be modified by oxidizing bitumen. All of the precursor bituminous materials mentioned in the present invention may be selected from commercially available products. The precursor biomass material includes one or more of a cellulose, a lignin, a starch, a chitosan, a sucrose, and a glucose. The pore structure of the bituminous hard carbon prepared from the precursor bituminous material of the present invention is more abundant and the pores are distributed uniformly, which is favorable for providing more lithium storage sites and improving the capacity of the composite material.
[0039] In some embodiments, the purpose of the heat treatment of the mixture in step S200 is to melt the precursor bituminous material and melt-coat the precursor bituminous material on the surface of the graphite. In this step, the mixture is heated at a first temperature, and the first temperature is equal to or higher than the melting point or softening point of the precursor bituminous material. For example, the precursor bituminous material is bitumen having a softening point of 150°C to 320°C. The first temperature is equal to or higher than the softening point of the bitumen. Specifically, the mixture is heated at 150°C to 320°C for 0.5h to 4h and kept at that temperature, and then the bitumen is melt-coated on the outer surface of the graphite.
[0040] Since the capacity of the hard carbon formed by carbonizing bitumen is low, the capacity of the composite material formed by coating graphite with hard carbon is relatively low, and in order to further improve the capacity of the composite material, a pore structure is formed inside the hard carbon during the process of forming the hard carbon, thereby increasing the lithium storage capacity. In some embodiments, the method further includes a step S500 of providing an organic solvent to the composite precursor to dissolve organic-soluble substances in the precursor, and a step S600 of removing the organic solvent by heating.
[0041] The inside of bitumen contains small molecular organic soluble substances, such as quinoline insolubles, and the organic solvent can dissolve a small amount of the organic soluble substances, which is favorable for forming a pore structure inside the bitumen after carbonization, providing more lithium ion active sites, and improving the capacity of the hard carbon. If the content of small molecular organic soluble substances in bitumen is too high, the organic solvent will dissolve many components, and the pore diameter of the pores formed in the hard carbon material will be too large to store lithium, so the mass content of quinoline insolubles in the bitumen is ≦5wt%. The mass content of quinoline insolubles was calculated based on the total mass of bitumen.
[0042] The bitumen with high carbon residue value contains a large amount of high molecular weight aromatic compounds on the surface and inside, and the volume change of the precursor bitumen material is low during the pyrolysis process, and the pores generated by the pretreatment remain, so that the carbon residue value of the bitumen is ≧50%. The precursor bitumen material needs to undergo thermal oxidation in step S300, and the pore structure inside the precursor bitumen material is fixed by oxidative crosslinking, so the softening point of the selected bitumen needs to be lower than the temperature for the oxidative crosslinking reaction. For example, the softening point of the bitumen is 150°C to 320°C.
[0043] In order to reduce the adverse effect of the organic solvent on the composite material, after the organic solvent dissolves the small molecule organic-soluble substances in the bitumen, the system is heated to volatilize and remove the organic solvent. The heating temperature in step S600 may be equal to or higher than the boiling point of the organic solvent. For example, the organic solvent may be one or more selected from halogenated hydrocarbons, alcohols, aromatic hydrocarbons, alicyclic hydrocarbons, and ketones.
[0044] Specifically, the composite precursor and the organic solvent are mixed at a concentration of 10 g / L to 200 g / L, stirred for 1 h to 48 h, and then suction filtered. The solid component is then placed in an oven at 60°C to 80°C for 12 h to 48 h.
[0045] In some embodiments, in step S300, the composite precursor is heated again to oxidize and crosslink the composite precursor, particularly to generate oxidative crosslinks inside the precursor bitumen material in the composite precursor, form a three-dimensional crosslinked network structure in the precursor bitumen material, and fix the internal structure of the precursor bitumen material. This step can be combined with steps S500 and S600 to form a three-dimensional crosslinked network pore structure in the precursor bitumen material, and obtain a hard carbon structure with a large amount of pore structure after carbonization, which is favorable for storing lithium ions, improves the capacity of the hard carbon material, and improves the capacity of the entire composite material.
[0046] The second temperature in step S300 should be lower than the melting point or softening point of the precursor bituminous material, for example, the precursor bituminous material is bitumen, whose softening point is 150° C. to 320° C. The second temperature is lower than the softening point temperature.
[0047] Specifically, the composite precursor is heat-treated in an oxidizing atmosphere at a temperature lower than the softening point temperature of bitumen, for example, at 140° C. to 300° C. for 0.5 h to 48 h, to sufficiently oxidize and crosslink the inside of the precursor bitumen material.
[0048] In some embodiments, step S400 carbonizes the crosslinked precursor, the carbonization temperature needs to be relatively high, and after carbonization and sintering, a hard carbon material is formed, and the hard carbon material forms a coating layer that covers the outer surface of the graphite. The crosslinked precursor is heated to 400°C-700°C in an inert atmosphere, kept at that temperature for 0.5h-4h, and then heated to 900°C-1400°C, kept at that temperature for 0.5h-4h, to obtain a composite material.
[0049] In one specific embodiment of the present invention, the steps of preparing the composite material include: (1) Crush and sieve bitumen to control the particle Dv50 to within the range of 1 μm to 4 μm. Mix the sieved bitumen and graphite with Dv50 in the range of 8 μm to 14 μm uniformly. After mixing, the small-sized bitumen particles are electrostatically adsorbed onto the surface of the large-sized graphite particles. After heat treatment, the bitumen particles melt and coat the surface of the graphite particles, thereby obtaining a composite precursor A in which the graphite is coated with bitumen. The mass ratio of bitumen to graphite in the mixing process is 0.01 to 2. (2) Precursor A obtained in step (1) is placed under an inert atmosphere, heated to a temperature within the range of 150°C to 320°C, and kept at that temperature for 0.5h to 4h to obtain precursor B. The temperature in this step must be higher than the melting temperature of bitumen. (3) Precursor B obtained in step (2) is mixed with an organic solvent in a ratio of 10 g / L to 200 g / L, stirred for 1 h to 48 h, and then suction filtered. The solid component is then placed in an oven at 60°C to 80°C for 12 h to 48 h to obtain precursor C, and the organic solvent is one or more of halogenated hydrocarbons, alcohols, aromatic hydrocarbons, alicyclic hydrocarbons, and ketones. (4) Precursor C obtained in step (3) is heat-treated in an oxidizing atmosphere within a temperature range of 150°C to 350°C for 0.5h to 48h to obtain precursor D, and the temperature in this step must be lower than the melting temperature of bitumen. (5) Precursor D obtained in step (4) is heated to 400°C to 700°C in an inert atmosphere, kept at that temperature for 0.5 h to 4 h, and then heated to 900°C to 1400°C and kept at that temperature for 0.5 h to 4 h to obtain a composite material in which a bituminous hard carbon layer covers graphite.
[0050] negative electrode piece A third aspect of the present invention provides an anode piece, the anode piece including an anode current collector and an anode active material layer disposed on at least one surface of the anode current collector, the anode active material layer including a composite material according to any one of the embodiments of the first aspect of the present invention or a composite material prepared by a method according to any one of the embodiments of the second aspect of the present invention.
[0051] In some embodiments, the negative electrode active material layer has a compressed density of 1.45 g / cm 3 ~1.7g / cm 3 Since the coating layer of the composite material contains a hard carbon material, the hard carbon material forms a large amount of pore structure during the preparation process, and the density of the entire composite material is not high. After coating it on the surface of graphite, the compression density of the negative electrode active material layer is relatively low with the increase in the amount of coating.
[0052] In some embodiments, the porosity of the negative electrode active material layer is in the range of 15% to 25%. When the cross-sectional porosity of the negative electrode active material layer is in the above range, the electrolyte can sufficiently wet the particles of the negative electrode active material, the dynamic properties can be improved, and the contact points between the particles of the negative electrode active material are relatively large, the internal resistance of the electrochemical device is relatively small, and the energy density of the electrochemical device can be ensured.
[0053] In some embodiments, the negative electrode piece configuration is any negative electrode piece configuration known in the art for use in electrochemical devices.
[0054] In some embodiments, the negative electrode current collector is a metal, such as, but not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a conductive metal coated polymer substrate, or a combination thereof.
[0055] The negative electrode active material may be a composite material according to any one of the embodiments of the first aspect of the present invention or a composite material prepared by the method according to any one of the embodiments of the second aspect of the present invention, and may be any conventionally known material capable of reversibly absorbing and releasing active ions or capable of reversibly doping and dedoping active ions, which can be used as a negative electrode active material for electrochemical devices known in the art.
[0056] In some embodiments, the negative electrode active material includes at least one of lithium metal, lithium metal alloy, carbon material, material capable of doping and dedoping lithium, or transition metal oxide. In some embodiments, the carbon material can be selected from various carbon materials known in the art that can be used as carbon-based negative electrode active materials in electrochemical devices. In some embodiments, the carbon material includes at least one of crystalline carbon and amorphous carbon. In some embodiments, the crystalline carbon is natural graphite or artificial graphite. In some embodiments, the crystalline carbon is amorphous, plate-shaped, flake-shaped, spherical, or fibrous. In some embodiments, the crystalline carbon is low-crystalline carbon or high-crystalline carbon. In some embodiments, the low-crystalline carbon includes at least one of soft carbon and hard carbon. In some embodiments, the high-crystalline carbon includes at least one of natural graphite, crystalline graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesocarbon microbeads, mesophase pitch, and high-temperature calcined carbon.
[0057] In some embodiments, the high-temperature calcined carbon is coke derived from petroleum or coal tar pitch. In some embodiments, the amorphous carbon includes at least one of soft carbon, hard carbon, mesophase pitch carbonization product, and calcined coke. In some embodiments, the negative electrode active material includes a transition metal oxide. In some embodiments, the transition metal oxide includes at least one of vanadium oxide and lithium vanadium oxide. In some embodiments, the negative electrode active material includes at least one of Si, SiOx (0 < x < 2), Si / C composite, Si-Q alloy, Sn, SnOz, Sn-C composite, and Sn-R alloy, where Q is selected from at least one of alkali metals, alkaline earth metals, Group 13-16 elements, transition elements, and rare earth elements, and Q is not Si, and R is selected from at least one of alkali metals, alkaline earth metals, Group 13-16 elements, transition elements, and rare earth elements, and R is not Sn. In some embodiments, Q and R include at least one of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po.
[0058] In some embodiments, the negative electrode active material layer further includes a negative electrode binder and a negative electrode conductive agent. In some embodiments, the negative electrode binder includes at least one of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, and nylon. In some embodiments, the negative electrode conductive agent may include any conductive material that provides electrical conductivity to the electrode and does not undergo chemical change. In some embodiments, the negative electrode conductive agent includes any one of carbon-based materials, metal-based materials, and conductive polymers, or a mixture thereof. In some embodiments, the carbon-based material includes at least one of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber. In some embodiments, the metal-based material includes at least one of metal powder or metal fiber, such as copper, nickel, aluminum, and silver. In some embodiments, the conductive polymer includes a polyphenylene derivative.
[0059] In some embodiments, the method for preparing the negative electrode pieces is a method known in the art for preparing a negative electrode for use in an electrochemical device. In some embodiments, when preparing the negative electrode slurry, a solvent, a negative electrode active material, and a binder are typically added, and a conductive material and a thickener are added as necessary, and then dissolved or dispersed in a solvent to prepare the negative electrode slurry. The solvent is volatilized and removed during the drying process. The solvent is a known solvent that can be used in the negative electrode active material layer, such as, but not limited to, water. The thickener is a known thickener that can be used in the negative electrode active material layer, such as, but not limited to, sodium carboxymethylcellulose.
[0060] In the present invention, the mixing ratio of the negative electrode active material, binder, and thickener in the negative electrode active material layer is not particularly limited, and can be controlled according to the desired characteristics of the electrochemical device.
[0061] Electrochemical Equipment The fourth aspect of the invention further provides an electrochemical device, said electrochemical device comprising a negative electrode piece, which may be selected from the negative electrode pieces of any of the embodiments of the third aspect of the invention.
[0062] In some embodiments, the electrochemical devices of the present invention include, but are not limited to, primary batteries, secondary batteries, fuel cells, solar cells, and capacitors.
[0063] In some embodiments, the electrochemical device is a lithium secondary battery.
[0064] In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, and a lithium ion polymer secondary battery.
[0065] [Positive electrode piece] The electrochemical device according to the embodiment of the present invention may further include a positive electrode piece. The positive electrode piece is a positive electrode piece known in the art for use in electrochemical devices. In some embodiments, the positive electrode piece includes a positive electrode current collector and a positive electrode active material layer. The positive electrode active material layer is disposed on a surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material.
[0066] In some embodiments, the cathode piece configuration is any cathode piece configuration known in the art for use in electrochemical devices.
[0067] In some embodiments, the positive electrode current collector is a metal, such as, but not limited to, aluminum foil.
[0068] The positive electrode active material may be any known material that can reversibly store and release active ions and can be used as a positive electrode active material for electrochemical devices. In lithium ion batteries, the positive electrode active material usually contains lithium ions, and in sodium ion batteries, the positive electrode active material usually contains sodium ions. Next, lithium ions will be taken as an example for explanation.
[0069] In some examples, the positive electrode active material comprises a positive electrode material capable of absorbing and releasing lithium, including, but not limited to, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium manganese oxide, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadyl phosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials.
[0070] In some embodiments, the positive electrode active material layer further includes a positive electrode binder and a positive electrode conductive agent. The positive electrode binder is used to improve the binding properties between the particles of the positive electrode active material and between the particles of the positive electrode active material and the current collector. In some embodiments, the positive electrode binder includes at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, and nylon. The positive electrode conductive agent is for imparting electrical conductivity to the electrode, and may be any material having electrical conductivity as long as it does not undergo chemical change. In some embodiments, the positive electrode conductive agent includes at least one of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal powder, metal fiber, and polyphenylene derivative. In some embodiments, the metal in the metal powder and metal fibers includes at least one of copper, nickel, aluminum, and silver.
[0071] In some embodiments, the method for preparing the positive electrode pieces is a method known in the art for preparing positive electrode pieces for use in electrochemical devices. In some embodiments, when preparing the positive electrode slurry, a solvent, a positive electrode active material, and a binder are typically added, and a conductive material and a thickener are added as necessary, and then the positive electrode slurry is prepared by dissolving or dispersing the positive electrode active material in a solvent. The solvent is volatilized and removed during the drying process. The solvent is a known solvent that can be used for the positive electrode active material layer, such as, but not limited to, N-methylpyrrolidone (NMP).
[0072] [Separator] The electrochemical device according to the embodiment of the present invention may further include a separator for preventing short circuit. The material and shape of the separator used in the embodiment of the present invention are not particularly limited and may be any technology disclosed in the prior art.
[0073] In some embodiments, the separator comprises a material, such as a polymer or inorganic material, that is stable with the electrolyte of the present invention.
[0074] In some embodiments, the separator includes at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyimide, and aramid. For example, the polyethylene includes at least one component selected from high density polyethylene, low density polyethylene, and ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have excellent short circuit prevention effects and can improve the stability of the battery due to the town-off effect.
[0075] The separator may further include a porous layer on the surface, the porous layer being provided on at least one surface of the separator, the porous layer including inorganic particles and a binder, the inorganic particles being one or more combinations selected from aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is one or a combination selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, sodium carboxymethylcellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.
[0076] The porous layer on the surface of the separator can improve the heat resistance, oxidation prevention and electrolyte wetting properties of the separator, and can strengthen the adhesion between the separator and the pole pieces.
[0077] The method of preparing the separator is any method known in the art for preparing separators for use in electrochemical devices.
[0078] [Electrolyte] The electrochemical device according to the embodiment of the present invention may further include an electrolyte solution. The electrolyte solution of the present invention contains an electrolyte salt. The electrolyte salt is an electrolyte salt known in the art that is suitable for the electrochemical device. For different electrochemical devices, appropriate electrolyte salts can be selected. For example, in lithium ion batteries, lithium salts are commonly used as electrolyte salts. Also, for example, in sodium ion batteries, sodium salts are commonly used as electrolyte salts. Next, an example of a lithium ion battery will be described.
[0079] In some embodiments, the lithium salt comprises or is selected from at least one of an organic lithium salt and an inorganic lithium salt. In some embodiments, the electrolyte further comprises a lithium salt, the lithium salt comprising lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, the concentration of the lithium salt being 1 mol / L-2 mol / L, and the molar ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate being 0.05-4.
[0080] In some embodiments, the electrolyte may further include a non-aqueous solvent, which may be a carbonate compound, a carboxylic acid ester compound, an ether compound, another organic solvent, or a combination thereof.
[0081] The carbonate compound may be a chain carbonate compound, a cyclic carbonate compound, a fluorocarbonate compound, or a combination thereof.
[0082] Examples of linear carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) or a combination thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or a combination thereof. Illustrative examples of the fluorocarbonate compound are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.
[0083] Illustrative examples of carboxylate compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, gamma-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or combinations thereof.
[0084] Illustrative examples of ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or combinations thereof.
[0085] Examples of other organic solvents are dimethylsulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters or combinations thereof.
[0086] The nonaqueous organic solvent in the electrolyte may be one nonaqueous organic solvent or a mixture of multiple nonaqueous organic solvents. When a mixed solvent is used, the mixing ratio can be controlled according to the desired electrochemical device characteristics.
[0087] The electrolyte of the present invention may further include a functional additive, such as a film-forming additive, a positive electrode film-forming additive. The film-forming additive can form an interface film on the surface of the negative electrode piece and / or the positive electrode piece to protect the negative electrode piece and / or the positive electrode piece. In some embodiments, the film-forming additive may be a polynitrile additive, a sulfonate additive, etc.
[0088] Based on the same inventive concept, the present invention further provides an electronic device.
[0089] The electronic device of the present invention may be any electronic device, such as, but not limited to, a laptop, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a mobile facsimile, a mobile copy machine, a mobile printer, a headphone stereo, a video recorder, a liquid crystal television, a handy cleaner, a portable CD player, a mini disc, a walkie-talkie, an electronic organizer, a calculator, a memory card, a mobile tape recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, an assisted bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a flashlight, a camera, a large-scale household storage battery, and a lithium-ion capacitor. In addition to the electronic devices exemplified above, the electrochemical device of the present invention can also be applied to an energy storage power plant, a marine transportation means, and an air transportation means. An air transportation means includes an air transportation means in the atmosphere and an air transportation means outside the atmosphere.
[0090] In some embodiments, the electronic device comprises an electrochemical device as described above in the present invention.
[0091] The following takes lithium ion battery as an example and refers to comparative examples and examples to further illustrate the technical solution of the present invention, but is not limited thereto. Those skilled in the art will understand that the preparation methods described in the present invention are only illustrative examples, and can make modifications or equivalent substitutions to the technical solution of the present invention without departing from the scope of the technical solution of the present invention, and should be included in the protection scope of the present invention.
[0092] Unless otherwise specified, all reagents, materials and instruments used in the following Examples and Comparative Examples are commercially available or can be obtained by synthesis.
[0093] Examples and Comparative Examples Example 1 Preparation of a Lithium-Ion Battery 1. Preparation of the positive electrode The positive electrode active materials, lithium cobalt oxide, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF), were mixed in a weight ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) was added as a solvent and stirred uniformly to form a positive electrode slurry. The positive electrode slurry (solid content 72 wt%) was uniformly coated on aluminum foil, the positive electrode current collector, to a coating thickness of 80 μm, dried at 85°C, and then cold-rolled, cut, and slit, and dried in a vacuum at 85°C for 4 hours to obtain positive electrode pieces.
[0094] 2. Preparation of negative electrode pieces 2.1 Preparation of negative electrode active material 1 g of bitumen material particles with Dv50 of 2 μm and 99 g of artificial graphite with Dv50 of 11 μm were placed in a V-type mixer and mixed for 2 h to obtain precursor A, in which the softening point of bitumen was 260°C, the residual carbon value was 75%, and the quinoline insoluble matter was ≦0.5%. The precursor A produced in the previous step was placed in an oven, heated to 280°C under a nitrogen gas atmosphere, and kept at that temperature for 3 hours to prepare precursor B, in which graphite was coated with bitumen. 50 g of the precursor B powder was mixed with 500 ml of toluene under stirring for 24 hours, and then suction filtered to collect the solid powder. The solid powder was then placed in an oven at 70° C. for 24 hours to obtain precursor C. Precursor C was placed in an oven, heated to 220° C. under compressed air, and kept at that temperature for 24 hours to obtain Precursor D. Precursor D was heated to 600°C under an argon gas atmosphere, kept at that temperature for 2 hours, then heated to 1100°C and kept at that temperature for 2 hours to obtain a composite material in which graphite was coated with a hard carbon layer. This composite material was used as the negative electrode active material.
[0095] 2.2 Preparation of negative electrode pieces The negative electrode active material prepared in step 2.1, the binder styrene butadiene rubber, and sodium carboxymethyl cellulose (CMC) were dissolved in deionized water in a weight ratio of 97:1.5:1.5 to form a negative electrode slurry (solid content 40 wt%). A 6 μm thick copper foil was used as the negative electrode current collector, and the negative electrode slurry was applied to the negative electrode current collector, the thickness of the applied single layer was 50 μm, dried at 85 ° C, cold rolled, cut, slit, and then dried under vacuum conditions at 120 ° C for 12 hours to obtain a negative electrode piece.
[0096] 3. Preparation of Separator The separator was polyethylene (PE) with a thickness of 7 μm.
[0097] 4. Preparation of Electrolyte Solution In a glove box with a dry argon gas atmosphere, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC:PC:DEC = 1:1:1, and 2 wt% of 1,3-propane sultone, 2 wt% of fluoroethylene carbonate, and 2 wt% of succinonitrile were added and dissolved. After sufficient stirring, lithium salt LiPF6 was added and mixed uniformly to obtain an electrolyte solution, where the concentration of LiPF6 was 1 mol / L.
[0098] 5. Preparation of Lithium-ion Batteries The positive electrode piece, separator, and negative electrode piece are stacked in order, and a separator is placed between the positive electrode piece and the negative electrode piece to play the role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an exterior aluminum laminate, and after removing moisture at 80°C, the above-mentioned electrolyte is poured in, sealed, and processed through formation, degassing, cutting, etc. to obtain a lithium-ion battery.
[0099] Examples 2 to 25 In Examples 2 to 25, lithium ion batteries were prepared in a manner similar to that of Example 1. The difference from Example 1 was that in Examples 2 to 25, the mass of the graphite component, the mass of the bitumen component, the Dv50 of the graphite component particles, and the Dv50 of the bitumen component particles were changed in the process of preparing the negative electrode active material, and the corresponding composite materials were prepared to prepare lithium ion batteries.
[0100] Comparative Example 1 In Comparative Example 1, a lithium ion battery was prepared in a manner similar to that of Example 1, except that the negative electrode active material in Comparative Example 1 was artificial graphite.
[0101] Comparative Example 2 In Comparative Example 2, a lithium ion battery was prepared in a manner similar to that of Example 1, except that the negative electrode active material in Comparative Example 2 was hard carbon. The method for preparing hard carbon is as follows: take bitumen material particles with Dv50 of 15μm, heat to 280℃ under nitrogen gas atmosphere and keep warm for 3h, to obtain bitumen precursor A, where the softening point of bitumen is 260℃, residual carbon value is 75%, and quinoline insoluble matter is ≦0.5%; 50g of precursor A powder is mixed with 500ml of toluene and stirred for 24h, then suction filtered, collect solid powder, and place in a 70℃ oven for 24h to obtain precursor B; precursor B is placed in the oven and heated to 220℃ under compressed air and kept warm for 24h to obtain precursor C; precursor C is heated to 600℃ under argon gas atmosphere and kept warm for 2h, then heated to 1100℃ and kept warm for 2h to obtain hard carbon.
[0102] Comparative Example 3 and Comparative Example 4 In Comparative Example 3 and Comparative Example 4, lithium ion batteries were prepared in a manner similar to that of Example 1. The difference from Example 1 is that in Comparative Example 3 and Comparative Example 4, at least one of the mass of the graphite component, the mass of the bitumen component, the Dv50 of the graphite component particles, and the Dv50 of the bitumen component particles was changed during the preparation process of the negative electrode active material.
[0103] Measuring part: 1. Measurement of relevant parameters of negative active material A fully discharged lithium ion battery was disassembled, and the removed negative electrode pieces were immersed in DMC (dimethyl carbonate) for 20 minutes, and then washed once each with DMC and acetone in order to remove the electrolyte and the surface SEI film, and then placed in an oven and heated at 80 ° C for 12 hours to obtain a treated negative electrode piece. The powder on the negative electrode piece was scraped off with a doctor blade, and the scraped powder was heat-treated at 400 ° C for 4 hours in a tubular furnace under argon gas protection conditions to remove the binder attached to the surface of the negative electrode active material, and the negative electrode active material was obtained. The following measurements were performed on the obtained negative electrode active material layer and negative electrode active material.
[0104] 1. Measurement of the ratio of the uncoated area to the coated area of the negative electrode active material The surface defect level of the negative electrode active material was measured using a laser microscopy confocal Raman spectrometer, and the 1350 cm -1 Peak intensity at I D and 1580cm -1 Peak intensity at I G Comparison with I D / I G The value indicates the surface defectivity of the sample. Each sample was measured at multiple locations, and the material properties were defined by the numerical magnitude of surface defects in different areas, I D / I G If the measured value is within the range of 0.01 to 0.4, it is defined as a graphite surface feature, counted as a, and I D / I G If the measured value is within the range of 0.7 to 1.4, it can be defined as a hard carbon surface feature and counted as b. The spatial resolution of the Raman test is sμm 2As can be seen from the law of large numbers, when there is a sufficient amount of measurement data, the value of a×s can be calculated as the area of the uncoated graphite in the negative electrode active material, i.e., the first area A1μm 2 The value of b×s can be approximated as the area of the hard carbon of the coating layer in the negative electrode active material, i.e., the second area A2 μm 2 and therefore the ratio of the uncoated area to the area of the coated layer is A1 / A2=a / b. The ratio A1 / A2 of the uncoated area of the negative active material to the area of the coating layer can be obtained by the following method. Ten samples of the same negative active material are taken, and 100 different points are measured for each sample. The obtained I D / I G The values a and b were obtained according to the magnitude of the value of a, and the ratio A1 / A2=a / b of the area of the non-coated negative electrode active material to the area of the coating layer was calculated.
[0105] 2. Measurement of the average thickness of the coating layer After embedding the negative electrode active material in epoxy resin and hardening it, the complete particles were cut out by ultra-thin sectioning to prepare samples. Cross sections of the particle samples were selected and observed under a high-magnification transmission electron microscope to observe the regions with long-range order, i.e., graphite. The amorphous regions (where there is no layer with long-range order and the layer arrangement is irregular) that cover the surface of the graphite, i.e., the hard carbon regions, were observed. The average thickness of the coating layer was measured multiple times.
[0106] 3. Measurement of characteristic peaks of negative electrode active materials by X-ray diffraction (XRD) The negative electrode active material was measured using an X-ray powder diffractometer (XRD, instrument model number: Bruker D8 ADVANCE), the target was CuKα, the voltage current was 40KV / 40mA, the scanning angle was in the range of 5° to 80°, the scanning step width was 0.00836°, and the time for each step width was 0.3s.
[0107] 4. Measurement of particle size of negative electrode active material The particle size of the powder of the negative electrode active material was measured using a Malvern particle sizer. The negative electrode active material was dispersed in an ethanol dispersant and ultrasonicated for 30 minutes, after which the sample was added to the Malvern particle sizer to measure the Dv50 of the negative electrode active material.
[0108] 5. Measurement of the specific surface area of negative electrode active material particles The specific surface area of the negative active material was measured by a nitrogen adsorption-desorption method using a specific surface area analyzer (Tristar II 3020M), and a sample of the negative active material was dried in a vacuum drying oven, placed in a sample tube, and measured with the analyzer.
[0109] 6. Measurement of capacity per gram of negative electrode active material and initial coulombic efficiency The initial reversible capacity per gram of the negative electrode active material at 0 V to 2.0 V can be determined by the following measurement method. A negative electrode piece with one side coated is taken and cut to a certain area to be used as a working electrode, then a lithium sheet (or sodium sheet, etc.) is used as a counter electrode, a porous polyethylene film is used as a separator, and an electrolyte is injected and assembled to obtain a button battery. The specific composition of the electrolyte is not specifically limited, and for example, the electrolyte can be a LiPF6 solution with a concentration of 1 mol / L, and the solvent can be obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1. The button battery was first discharged to 0V at three small currents of 0.05C / 50μA / 20μA, respectively, and the initial discharge capacity of the button battery was recorded. Then, it was charged to 2.0V at a constant current of 0.1C, and the initial charge capacity of the button battery was recorded. Initial coulombic efficiency = initial charge capacity / initial discharge capacity × 100%; Initial reversible capacity per gram of the negative electrode active material from 0 V to 2.0 V = Initial charging capacity of button battery / Mass of negative electrode active material
[0110] Second, measurement of relevant parameters of negative electrode 7. Measurement of porosity of negative electrode active material layer The negative electrode active material layer samples were prepared in the form of perfectly circular sheets. In each Example or Comparative Example, 30 samples were measured, and the volume of each sample was approximately 0.35 cm. 3 The porosity of the negative electrode active material layer was measured according to the standard "GB / T24586-2009 Measurement of apparent density, true density, and porosity of iron ore".
[0111] 8. Measurement of the compression density of the negative electrode active material layer A fully discharged lithium ion battery was taken, and the negative electrode piece was disassembled, washed, and dried. A negative electrode piece (both sides of the negative electrode current collector were coated with a negative electrode active material layer) of a certain area S was weighed on an electronic balance, the weight was designated as P1, and the thickness T1 of the negative electrode piece was measured in ten-thousandth micrometers. The negative electrode active material layer was washed off with a solvent and dried, and the weight of the negative electrode current collector was measured, the weight was designated as P2, and the thickness T2 of the negative electrode current collector was measured in ten-thousandth micrometers. The weight W0 and thickness T0 of the negative electrode active material layer disposed on one side of the negative electrode current collector, and the compressed density of the negative electrode active material layer were calculated according to the following formulas. P0 = (P1 - P2) / 2; T0=(T1-T2) / 2; Compressed density = P0 / (T0 x S).
[0112] 3. Measurement of Lithium-ion Battery Characteristics 9. Measurement of energy density of lithium-ion batteries Five lithium-ion batteries were removed from each set. First, in an environment of 25°C, the first charge and discharge were performed, followed by constant current charging and constant voltage charging at a charging current of 0.5C until the upper limit voltage reached 4.48V, and then constant current discharging was performed at a discharge current of 0.2C until the discharge end voltage was 3V. Based on the measurement results, the lithium-ion battery capacity, discharge platform voltage, and volumetric energy density of the lithium-ion battery = lithium-ion battery capacity × discharge platform voltage / lithium-ion battery volume were calculated, and the percentage of volumetric energy density relative to Comparative Example 1 was calculated for each Example and Comparative Example.
[0113] 10. Measurement of charging rate characteristics of lithium-ion batteries Five lithium-ion batteries were removed from each set. The battery was repeatedly charged and discharged according to the following steps, the capacity (average value) at each charging stage was statistically recorded, and the percentage of the capacity at the CC stage was calculated. The specific steps were as follows: First, the battery was left in an environment of 25°C for 1 hour. The battery was charged with constant current (CC) at a charging rate of 1C, charged to 4.48V, and then converted to constant voltage (CV) charging. When the charging current was lower than 0.05C, charging was stopped and the battery was left for 5 minutes. Then, the battery was discharged with a constant current of 0.2C to 3V and left for 5 minutes to ensure the integrity of the subsequent charging and discharging processes. Then, the battery was fully charged according to the previous CC+CV charging mode at different rates such as 0.2C, 0.5C, 1C, 2C, 3C, etc., and after leaving it for 5 minutes, the battery capacity was fully discharged at a rate of 0.2C, and the capacity percentage of the CC stage at different charging rates was calculated. The measurement is performed according to the previous CC+CV charging mode at a rate of 3C, and the battery is fully charged. The calculation formula is as follows: Percentage of CC segment capacity (3C) = [CC segment charge capacity / (CC+CV) total charge capacity] x 100%
[0114] 11. Measurement of low-temperature characteristics of lithium-ion batteries Five lithium-ion batteries were removed from each set. First, the first charge and discharge were performed in an environment of 25°C, and constant current and constant voltage charging was performed with a charging current of 0.5C, continuing until the upper limit voltage reached 4.48V, then constant current discharging was performed with a discharge current of 0.2C, the discharge end voltage was 3V, and the average capacity A of the lithium-ion battery was measured, then the environmental temperature was lowered to -20°C and left to stand for 1 hour, and the average capacity B of the lithium ion was measured in an environment of -20°C according to the above steps, and the capacity retention rate of the lithium-ion battery at -20°C = B / A x 100%.
[0115] 12. Measurement of cycle characteristics of lithium-ion batteries Five lithium-ion batteries were removed from each set. The lithium ion battery was repeatedly charged and discharged in the following steps, and the discharge capacity retention rate and thickness expansion of the lithium ion battery were calculated. First, the first charge and discharge were performed in an environment of 25°C. Constant current charging was performed at a charging current of 1C until the upper limit voltage reached 4.48V, after which the charging was changed to constant voltage charging, and then constant current discharging was performed at a discharge current of 1C until the final voltage reached 3V. The discharge capacity of the first cycle and the thickness of the fully charged cell were recorded, and then 400 charge / discharge cycles were performed, and the discharge capacity of the 400th cycle and the thickness of the fully charged cell were recorded. Cycle capacity retention rate = (discharge capacity at 400th cycle / discharge capacity at first cycle) x 100% Cell thickness expansion with cycling = (cell thickness at 400th cycle full charge / cell thickness at 1st cycle full charge) x 100%
[0116] Measurement results The relevant parameters of the examples and comparative examples are as shown in Tables 1 and 2.
[0117] [Table 1]
[0118] [Table 2]
[0119] As can be seen from Tables 1 and 2, graphite was used as the negative electrode active material in Comparative Example 1, and bituminous hard carbon was used as the negative electrode active material in Comparative Example 2. In Examples 1 to 25, Comparative Examples 3 and 4, a composite material in which graphite was coated with a bituminous hard carbon layer was used as the negative electrode active material.
[0120] As can be seen from Examples 1 to 25, Comparative Example 3 and Comparative Example 4, as the mass ratio of bitumen, which is a coating component, increases, the ratio A1 / A2 of the uncoated area to the area of the coating layer decreases, and the average thickness H of the coating layer increases, but after the mass ratio of the bitumen component increases to a certain amount, blocking between particles occurs during the melting process, which requires crushing and sieving, and the coating interface is exposed during the crushing process. In the examples with a high content of the bitumen component in the coating, the specific surface area and capacity per gram of the composite material are both improved, but the initial coulombic efficiency is reduced, which is because the hard carbon material has many defects and pores, which is also the reason why the compressed density of the negative electrode active material layer in the corresponding examples is low and the porosity is large. A lithium ion battery prepared with a composite material synthesized by combining graphite and bitumen with an appropriate mass ratio of the coating component bitumen and an appropriate particle size can obtain a higher energy density, and at the same time, the rapid charging ability, low temperature capacity retention rate and long cycle characteristics of the lithium ion battery are all improved.
[0121] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above described embodiments should not be construed as limiting the present invention, and that modifications, substitutions and alterations can be made to the embodiments without departing from the spirit, principle and scope of the present invention.
Claims
1. A graphite particle is included, and a first region and a second region are included on a surface of the graphite particle, the first region is graphite, the second region includes a hard carbon layer, and a surface area of the first region is A 1 μm 2 and the surface area of the second region is A 2 μm 2 When the above A 1 and the above A 2 That is, 0≦A 1 / A 2 ≦1.17, and when the thickness of the hard carbon layer is H nm, H satisfies 5≦H≦500.
2. The composite material according to claim 1 , wherein H satisfies 5≦H≦200.
3. The X-ray diffraction pattern of the composite material has a diffraction peak characteristic of hard carbon between 18° and 30°, and the half-value width of the diffraction peak characteristic of hard carbon is 4° to 12°; 2. The composite material according to claim 1, wherein the X-ray diffraction pattern of the composite material further has a diffraction peak characteristic of graphite between 26° and 27°.
4. The Raman spectrum of the composite material has a characteristic peak D and a characteristic peak G, and the peak intensity of the characteristic peak D is I D and the peak intensity of the characteristic peak G is I G Then, I D / I G is 0.05≦I D / I G 2. The composite material of claim 1, wherein the composite material satisfies ≦1.
4.
5. The specific surface area BET of the composite material is Sm 2 The composite material according to claim 1 , wherein S satisfies 0.5≦S≦8 when expressed as 1 / g.
6. A method for preparing a composite material according to any one of claims 1 to 5, comprising the steps of: a precursor bituminous material and graphite are mixed to form a mixed system, and in the mixed system, a ratio of a mass content of the precursor bituminous material to a mass content of the graphite is 0.01 to 1; heat-treating the mixture at a first temperature to melt the precursor bituminous material and coat it on an outer surface of the graphite to form a composite precursor, the first temperature being equal to or higher than a melting point or softening point of the precursor bituminous material, and the precursor bituminous material having a volume average particle size Dv50 of 0.5 μm to 5.0 μm; providing an organic solvent to the composite precursor to dissolve organic soluble materials in the composite precursor; heating to remove the organic solvent; heat treating the composite precursor at a second temperature to oxidatively crosslink the composite precursor to form a crosslinked precursor, the second temperature being below a melting point or softening point of the precursor bituminous material; heating the crosslinked precursor to 400°C to 700°C in an inert atmosphere, maintaining the temperature for 0.5h to 4h, and then increasing the temperature to 900°C to 1400°C and maintaining the temperature for 0.5h to 4h to carbonize the crosslinked precursor to obtain a composite material; The precursor bituminous material comprises one or more of petroleum asphalt, mesophase pitch, and modified asphalt; and The precursor bituminous material comprises: (1) the precursor bituminous material has a softening point of 150°C to 320°C; (2) the precursor bituminous material has a residual carbon value of ≧50%; (3) the mass content of quinoline insolubles in the precursor bituminous material is ≦5 wt %; and A method for preparing a composite material, the method satisfying one or more of the following requirements:
7. A negative electrode piece comprising: a negative electrode current collector; and a negative electrode active material layer provided on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising the composite material according to any one of claims 1 to 5.
8. The compressed density of the negative electrode active material layer is 1.45 g / cm 3 ~1.7g / cm 3 and / or The negative electrode piece according to claim 7 , wherein the porosity of the negative electrode active material layer is in the range of 15% to 25%.
9. 10. An electrochemical device comprising an anode piece, the anode piece comprising the anode piece of claim 7.
10. An electronic device comprising the electrochemical device of claim 9.
Citation Information
Patent Citations
Carbon material for lithium ion secondary battery, negative electrode material for lithium ion secondary battery, and lithium ion secondary battery
JP2013077530A
Carbonaceous material-coated graphite particle, manufacturing method thereof, negative electrode for lithium ion secondary batteries, and lithium ion secondary battery
JP2014167906A
Negative electrode for nonaqueous electrolyte solution based electrochemical element, method for manufacturing the same, lithium ion secondary battery, and method for manufacturing the same
JP2018081753A
Cathode material for lithium secondary battery, process for manufacturing the same, and secondary battery using the same
WO1997018160A1